Penerapan SOP dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Bakery di Kota Palembang - Jhon, Fernando (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the effect of implementing standard operational procedures and leadership styles on employee performance in bakeries in Palembang City. The research population was bakery shop employees in Palembang City. The sample used was 111 bakery shop employees in Palembang City using the purposive sampling method. The data analysis techniques used are descriptive analysis, research instrument testing, classical assumption testing, and multiple linear regression analysis